Evaluation Of Life Safety Equipment At KMP. Powder On A Cross Hunimua-Waipirit In Central Maluku District Maluku Province - Surnata Surnata; Sri Kelana; Jeri Family Lubis (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2021)
The Hunimua-Waipirit crossing route connects Ambon Island with West Seram Island in the travel time of 1.5 hours and on this route there is a KMP. Terubuk with the life safety equipment that is not in accordance with the rules regarding conditions and numbers. Inadequate equipment in the form of lifeboats, lifejackets, lifebuoys, and need the maintenance on the liferaft. The collection of inventory data for life safety equipment is carried out by observing at the KMP Terubuk, in order to obtain clear information regarding the condition and number of life safety equipment that do not comply with existing regulations. The results of the survey at KMP.Terubuk show that life safety equipment such as life jackets, lifebuoys, lifeboats had damaged and insufficient numbers and liferafts need to be checked and maintained. Owners need to increase the number of life jackets, lifebuoys, lifeboats and the captains need to check and maintenance schedule for life safety equipment. Because if the condition and number of life safety equipment are in accordance with the rules, if an accident occurs it can reduce the risk of the number of fatalities.